ORGANIZATION MANAGEABILITY ENHANCED THROUGH TOPOLOGICAL MODULAR FORMS - NANTOI, Daria; NANTOI, Vadim (Journal of Social Sciences)
Organizational manageability is a crucial aspect of business management, requiring a combination of forecasting, planning, organizing, implementing, controlling and decision-making. Topological modular forms study the properties of objects that are invariant under certain types of transformations and the authors search for and identify a set of key factors that are essential to the organizational manageability (both stable and unstable) and create a framework that captures these factors. Organizational manageability is highly complex and multifaceted field that requires the integration of mentioned elements. In order to simplify incommensurable complexity, authors offer the hypothesis that differentiating the approach to manageability in the two distinct situations "steady and familiar condition" and "unsteady and with considerable uncertainty condition" is effective. Discrimination between those two situations is essential for business success and requires a deep understanding of market trends, customer needs, design of organization and usage of resources. By mastering the principles of organizational manageability based on mentioned classification of situations, businesses can improve their performance, increase their competitiveness and achieve their goals more effectively.